Defense-related employment and spending, 1996-2006. - Thomson, Allison (Monthly Labor Review, 1998)
Between 1987 and 1996, defense-related spending and employment were severely curtailed. These cuts were felt across most industries and occupations in the U.S. economy. The huge reductions in defense spending and related employment are starting to show indications of slowing, however. The rate at which real defense spending is estimated to decline from 1996 to 2006 is substantially slower than the rate at which it fell during the previous decade. Statistics on defense spending and employment projected to 2006 are presented.